1999
DOI: 10.1139/f99-006
|View full text |Cite
|
Sign up to set email alerts
|

Estimating physiological cost of chemical exposure: integrating energetics and stress to quantify toxic effects in fish

Abstract: We present empirical support for a conceptual framework in which chemical contaminants are considered as sources of physiological stress to fish. Physiological stress was quantified in terms of energy by measuring routine metabolism, food consumption, activity, and growth rates of largemouth bass (Micropterus salmoides) exposed to the organochlorine pesticide dieldrin. Regression analysis was used to estimate models that describe the response of each endpoint as a function of dieldrin concentration and duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(41 citation statements)
references
References 10 publications
3
38
0
Order By: Relevance
“…The process may be initiated by reaction of MeHg with thiol (-SH) and/or selenol (-SeH) groups which caused formation of S-Hg or Se-Hg bond that may impair protein function in organism (Farina, Campos, Vendrell, Berenguer, Barzi, Pons & Sunol 2009). These could occur when fish expends most of their body energy for repairing damaged cells within allocated dietary energy which might hinder somatic and reproductive growth (Beyers, Rice, Clements & Henry 1999;Houck & Cech 2004). Similar result was found when beluga sturgeon, Huso huso, were fed 16.22 mg MeHg kg À1 diet for 6 weeks (Gharaei, Esmaili, Jafari & Ghaffari 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The process may be initiated by reaction of MeHg with thiol (-SH) and/or selenol (-SeH) groups which caused formation of S-Hg or Se-Hg bond that may impair protein function in organism (Farina, Campos, Vendrell, Berenguer, Barzi, Pons & Sunol 2009). These could occur when fish expends most of their body energy for repairing damaged cells within allocated dietary energy which might hinder somatic and reproductive growth (Beyers, Rice, Clements & Henry 1999;Houck & Cech 2004). Similar result was found when beluga sturgeon, Huso huso, were fed 16.22 mg MeHg kg À1 diet for 6 weeks (Gharaei, Esmaili, Jafari & Ghaffari 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to acidic conditions reduces the seawater tolerance of smolts, and those ill-prepared for the transition to seawater exhibit high levels of stress and reduced survival (Staurnes et al 1996;Kroglund and Finstad 2003;Kroglund et al 2007). Further, physiological stress may induce lethargy in fish (Sangalang et al 1990;McCormick and Jensen 1992;Beyers et al 1999), and smolts have been shown to delay sea entry if they are osmotically ill-prepared (Strand et al 2011). It, therefore, stands to reason that altered migratory behaviour would extend into the estuary in an attempt to mitigate poor seawater tolerance.…”
Section: Influence Of Behaviour On Survivalmentioning
confidence: 99%
“…For example, several species of herbivorous insects, which are important food for many insectivorous birds, may increase in numbers in a moderately polluted environment, but tend to be less abundant in heavily polluted areas (Fü hrer 1985, Heliö vaara andVäisänen 1990). Both food deprivation and environmental pollutants such as heavy metals are known to cause physiological stress, depressed metabolic rates, and retarded growth in birds and fish (Hutton 1980, Di Giulio and Scanlon 1985, Heath 1995, Beyers et al 1999. We report here an experimental study in which the amount of available invertebrate food was manipulated in an area heavily contaminated by metals.…”
Section: Introductionmentioning
confidence: 99%